Importance of Soil and Moisture Conservation in Increasing Agricultural Production - Mansingh, B. (Journal of Soil and Water Conservation, 2022)
Soon after laying special emphasis on Heavy Industries in the Second Five Year Plan, one of the principal objects of which was to provide employment to the ever increasing number of the unemployed and thus to lessen the pressure on land, the framers of the plan realized that increased agricultural production should receive first priority in order to feed the industries and to put a check on the inflationary tendencies in the country.